Preaching Strategy of KH. Abdul Rasyid Abdullah Syafi'ie on Alaikassalam Jakarta Radio - Muhammad Febiandri Satya Ananda; Abd Rozak (CV. Publikasi Indonesia, 2024)
Abdul Rasyid Abdullah Syafi'ie was a preacher and one of the great scholars who became a role model for the Betawi community. KH. Abdul Rasyid Abdullah Syafi'ie was the son of one of the great Betawi scholars, KH. Abdullah Shafi'ie. As a preacher of KH. Abdul Rasyid Abdullah Syafi'ie invited all people to practice Islamic law through various media, one of which was using radio media Alaikassalam Jakarta. The purpose of this study is to find out the strategy of Da'wah KH. Abdul Rasyid Abdullah Syafi'ie via Radio Alaikassalam Jakarta. This research was conducted using qualitative methods and descriptive data analysis methods. This method serves as a procedure for tracing the problem under study by describing the subject and object of research based on facts in the field. Then, the data collection techniques used are observation, interviews, and documentation. Based on the results of the study, the da'wah strategy used by KH. Abdullah Syafi'ie held an Islamic nuanced event on Radio Alaikassalam Jakarta and broadcast live the ta'lim assembly activities held at Al-Barkah mosque, Tebet, South Jakarta.